The Matter which may be: Sectarian Dilemmas of Materiality in Bahrain - Fibiger, Thomas (Material religion, 2019)
This article discusses different approaches to materiality and material expressions of cultural identity in contemporary Bahrain, a small Arab Gulf state. Various Islamic traditions have different understandings of materiality and its ontological qualities. In the contemporary Gulf this difference is often understood as a sectarian difference between Sunni and Shia Muslims, a division that has gained increasing political importance in recent years. In this article I discuss how these traditions view materiality in religion, in particular focusing on the role of material mediation for Shia Muslims, exemplified by the use and meaning of the turba prayer stone. With this as a point of departure I discuss two other forms of materialitypolitical graffiti and martyr imagesthat in the wake of the uprising in 2011 have also been imbued with sectarian meanings, but where this is less clear. I therefore argue that vernacular understandings of material culture show ambiguous identifications that challenge the clear dichotomies with which peoplelocally and analytically often operate.